Factors Predicting Central Details in Alleged Child Sexual Abuse Victims' Disclosure. Issue 3 (26th May 2016) - Alonzo-Proulx, Agnès; Cyr, Mireille
ABSTRACT: The purpose of this study is to explore the predictive value of child sexual abuse characteristics (relationship between the child and the suspect, reported coercion, type and frequency of abuse) as well as the disclosure context (disclosure made on purpose or accidentally, maternal belief, and protective actions) on the number of central forensically relevant (CFR) details elicited during the investigative interview of alleged child victims. The effects of the child's age and use of the National Institute of Child Health and Human Development (NICHD) Investigative Protocol were controlled for, in order to focus on the aspects of the sexual abuse and disclosure variables. Of the 116 investigative interviews conducted with children aged from 4 to 14 years old, half followed the NICHD Protocol; the other half were conducted by the same 18 interviewers prior to their training in the NICHD protocol. Police files and interview transcripts were analyzed to collect information about the child sexual abuse characteristics, the disclosure context, and the number of CFR details. As expected, the child's age and use of the NICHD Protocol were the two strongest predictors of the number of CFR details. Coercion (physical and verbal) as well as maternal protection following the disclosure also increased the number of CFR details. Explanations of these results and implications for further research are discussed.